10p-2(3p-6)=4(3p-6)-8p

Simplify each term.

Apply the distributive property.

10p-2(3p)-2⋅-6=4(3p-6)-8p

Multiply 3 by -2.

10p-6p-2⋅-6=4(3p-6)-8p

Multiply -2 by -6.

10p-6p+12=4(3p-6)-8p

10p-6p+12=4(3p-6)-8p

Subtract 6p from 10p.

4p+12=4(3p-6)-8p

4p+12=4(3p-6)-8p

Simplify each term.

Apply the distributive property.

4p+12=4(3p)+4⋅-6-8p

Multiply 3 by 4.

4p+12=12p+4⋅-6-8p

Multiply 4 by -6.

4p+12=12p-24-8p

4p+12=12p-24-8p

Subtract 8p from 12p.

4p+12=4p-24

4p+12=4p-24

Subtract 4p from both sides of the equation.

4p+12-4p=-24

Combine the opposite terms in 4p+12-4p.

Subtract 4p from 4p.

0+12=-24

Add 0 and 12.

12=-24

12=-24

12=-24

Since 12≠-24, there are no solutions.

No solution

Solve for p 10p-2(3p-6)=4(3p-6)-8p